1996
DOI: 10.1002/(sici)1096-9071(199609)50:1<82::aid-jmv14>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Detection of both herpes simplex and varicella‐zoster viruses in cerebrospinal fluid from patients with encephalitis

Abstract: Cerebrospinal fluid (CSF) samples from 46 patients with encephalitis were studied for the presence of herpes simplex virus (HSV) types 1 and 2 and/or varicella zoster virus (VZV)-specific DNA sequences by the polymerase chain reaction (PCR) assay. Patients were studied because of detection of intrathecal production of IgG antibody to HSV alone (10 patients, Group A) or to both HSV and VZV (11 patients, Group B) or because of the presence of specific anti-HSV IgG in CSF without evidence of intrathecal antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…A tentative diagnosis of HSV encephalitis can be performed by the demonstration of intrathecally produced anti-HSV antibodies as expressed in an increased ratio of HSV CSF and serum antibodies. By using immunoprecipitation, radioimmunoassay, enzyme-linked immunosorbent assay (ELISA), and immunoblotting, several authors suggested that an increased CSF-toserum antibody ratio is a reliable measure for the diagnosis of HSV encephalitis (5,10,15,20,26,31). By contrast, other authors hypothesized that prolonged antigen stimulation is present in the CNS after acute HSV encephalitis and that serological measurements combined with immunoglobulin and albumin determinations provide only a tentative, not definite, diagnosis (18).…”
mentioning
confidence: 99%
“…A tentative diagnosis of HSV encephalitis can be performed by the demonstration of intrathecally produced anti-HSV antibodies as expressed in an increased ratio of HSV CSF and serum antibodies. By using immunoprecipitation, radioimmunoassay, enzyme-linked immunosorbent assay (ELISA), and immunoblotting, several authors suggested that an increased CSF-toserum antibody ratio is a reliable measure for the diagnosis of HSV encephalitis (5,10,15,20,26,31). By contrast, other authors hypothesized that prolonged antigen stimulation is present in the CNS after acute HSV encephalitis and that serological measurements combined with immunoglobulin and albumin determinations provide only a tentative, not definite, diagnosis (18).…”
mentioning
confidence: 99%
“…Another possible interpretation of the presence of antibodies to both HSV-1 and VZV in CSF samples would be a response to dual infections. This was suggested in a study of 46 patients with suspected HSE in which 7/46 patients had both VZV DNA and HSV 1-DNA detected in the CSF samples by qualitative PCR (3).…”
mentioning
confidence: 95%
“…Virological confirmation is required in the case of zosteriform herpes simplex and in atypical VZV and HSV infections of immunosuppressed patients (1). Both primary and recurrent HSV or VZV infections may lead to CNS infection and disease (2).…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity and specificity may vary with different primer pairs and the genetic variability of naturally occurring strains of viruses is an important influencing factor. Many different primer pairs have been suggested for the diagnosis of HSV and VZV infections (1,2,8,(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%